Pengaruh Penambahan Ekstrak Biji Kelor Kering (Moringa oleifera Lam) dalam Pengencer Beltsville Thawing Solution terhadap Kualitas Semen Cair Babi Landrace - Pandahuki, Fransiska Onya; Nalley, W. Marlene; Uly, Kirenius; Mata Hine, Thomas (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this research was to determine the effect of adding dry moringa seed extract (DMSE) added to the Beltsville thawing solution (BTS) diluent on the quality of landrace boar semen during storage. This research used experimental methods and a completely randomized design consisting of 5 treatments and 5 replications to form 25 experimental units. The treatment in question was : T0 = BTS EY + 0% DMSE, T1 = BTS EY + 1% DMSE, T2 = BTS EY + 2% DMSE, T3 = BTS EY + 3% DMSE, T4 = BTS EY + 4% DMSE. This diluted semen will be stored at a temperature of 18-20ºC and evaluation of motility, viability, abnormalities and survival of spermatozoa was carried out every 8 hours of storage. Data was analysis of the average, standard deviation, variance and continued with the Duncan test. The results showed that T2 treatment with a 2% DMSE level at 32 hours of storage gave the best results (P<0.05) compared to other treatments, with motility values (51, 80±4.71), viability (65.54±5.00), abnormality (5.81±0.81 and survival value of (38.89±1.21). It was concluded that the addition of EBKK at a level of 2% to the BTS diluent provided a good response in maintaining motility, viability and abnormalities.